How International Trade, Investment, and Exports Affect GDP Growth - Sutikno, Suci Kartika Sari (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This study aims to empirically examine the impact of exports, imports, and foreign direct investment (FDI) on economic growth in five ASEAN countries Indonesia, Malaysia, Brunei Darussalam, the Philippines, and Timor-Leste over the period 2014–2023. The research employs secondary panel data sourced from the World Bank and applies panel data regression analysis. Model selection is conducted using the Chow test, Hausman test, and Lagrange Multiplier test, which collectively indicate that the Common Effect Model (CEM) is the most appropriate specification. The empirical results reveal that exports, imports, and FDI do not have a statistically significant effect on economic growth, either individually or simultaneously. Exports exhibit a negative but insignificant relationship with economic growth, suggesting structural weaknesses in export composition. Imports show a positive yet insignificant effect, indicating that imported goods may not sufficiently enhance domestic productive capacity. Meanwhile, FDI demonstrates a very weak and statistically insignificant contribution, implying limited spillover effects on host economies during the study period. The coefficient of determination (R²) of 3.59% indicates that only a small proportion of economic growth variation is explained by the three variables, highlighting the dominant role of other structural and institutional factors. These findings suggest that economic growth in ASEAN countries is influenced more strongly by variables beyond trade flows and foreign investment, such as human capital development, institutional quality, technological innovation, and domestic investment. Therefore, policy strategies should move beyond trade and investment expansion alone and focus on strengthening structural foundations to achieve sustainable economic growth.